Vocational Students’ Engagement in Digital Comic Strip Assisted Reading Comprehension - Elih Sutisna Yanto; Sopiatul Umah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the involvement of students in understanding English-language digital comic strips at the Sanggabuana Science and Technology Vocational School based on indicators of behavior, cognitive, and emotion. The participants in this study were tenth grade students of Sanggabuana Science and Technology Vocational School with two different genders; girls and boys. Data collection techniques used by researchers are using thematic analysis techniques, and data collection techniques using interviews, observation, and documentation. The results of the study showed that the involvement of Sanggabuana Science and Technology Vocational High School students that digital comic strips are media that are positively received by students at the school, they argue that digital comic strip is understanding medium because its contain pictures and storyline.